Comparative study of the effect of atorvastatin and garlic extract in experimentally induced hypercholesterolemia in rabbits - Dalal, Indrani; Sengupta, Mohua; Paul, Suhrita; Mishra, A. N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The abundant resource of drugs and its beneficial properties are hidden in our natural and Indigenous sources, which are under constant evaluation by man. Cholesterol lowering ability of ethanol extract of garlic was evaluated in comparison to atorvastatin, the most frequently used lipid lowering agent in rabbits. Methods: Hypercholesterolemia was induced to the animals with cholesterol powder (50mg/kg) for the study duration (16 weeks). At the end of 4 weeks, they were randomly selected and divided into 3 groups (n=6). Group II received Cholesterol + atorvastatin 10 mg daily; Group III received Cholesterol + 0.1g garlic extract kg b. w. daily while Group I continued with cholesterol powder (to serve as control) for the rest study period. Serum cholesterol, LDL, HDL and Triglycerides were estimated using the enzymatic method at 0, 4, 8, 12, 16 weeks in all the groups. The results were tabulated and analyzed statistically using one way ANOVA test. Results: The results indicate that both atorvastatin and garlic extract have a definite role in retarding the rate of weight gain as a consequence to high cholesterol diet in rabbits. Also, there is fewer rises in all the lipid parameters in both the treatment groups when compared to the control group. Conclusion: Though atorvastatin is definitely more effective in reducing the lipid parameters but it also significantly lowers HDL where as Garlic shows promising results when compared to placebo and also has a favourable effect on HDL. Garlic can be recommended as a dietary supplement for long term use without toxic effects for its wide range of medicinal properties in general and therapeutic potential inpatients with CAD in particular.